Pengaruh Rasio Keuangan Terhadap Earning Per Share: Studi Sektor Makanan dan Minuman di Indonesia - Hidayat, Famelia Widya; Zaman, Badrus; Kurniawan, Andy (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
This study aims to analyze the effect of Current Ratio (CR), Debt to Asset Ratio (DAR), and Inventory Turnover on Earning Per Share (EPS). This research employs a quantitative method with a causal-comparative ex-post facto approach. The population includes food and beverage companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2023 period. The sampling technique used purposive sampling, resulting in 10 companies with a total of 40 observations. Data analysis was conducted using multiple linear regression utilizing SPSS version 25 software. The results indicate that partially, CR, DAR, and Inventory Turnover each have a significant effect on EPS. Simultaneously, these three independent variables significantly affect EPS with a determination coefficient of 83.7%. The implications of this study emphasize the importance of liquidity management, solvency, and inventory efficiency in improving corporate share profitability.